Effect of Water on the Ripening of Pericarp Disks from Tomato Fruits - Simons, David H. (1973)
Color change, a measure of the ripening of pericarp disks of tomato fruits (Lycopersicon esculentum Mill. cv. Moneymaker), was delayed by osmotic water uptake. An even greater delay occurred when substances from the disks were allowed to leach out or to diffuse into agar, indicating the existence of a water-soluble substance(s) necessary for the ripening process. Osmotic solutions, allowing for more leaching, were more inhibitory to color development than the same amount of distilled water. The ripening process of tomato fruit disks can thus be disturbed by such processes as washing, infiltration, or incubation with solutions.